Synthesis structure-activity relationships and biological evaluation of optimised terminally alkylated (bis)urea and (bis)thiourea polyamine analogues as antiplasmodial agents - Birkholtz, Lyn-Marie (University of Pretoria, 2017)
Dissertation (MSc)--University of Pretoria, 2017.